SYNTACTIC ANALYSIS OF ARABIC NOUN PHRASE’S BETWEEN ARABIC AND ENGLISH: X BAR THEORY - Ohod Faisal Ahmed (Translation and Linguistics (Transling), 2023)
Through the prism of X-Bar theory, this research explores the complex world of Arabic nounphrases, contrasting and comparing their syntactic patterns with those of the English language. A keycomponent of linguistic study is the examination of noun phrases since it reveals the structuraldifferences and similarities between Arabic and English, two linguistically dissimilar languages. Themain goal of this research is to analyse how the distinctive structural characteristics of Arabic nounphrases differ from those of their English counterparts while taking into account the X-Bar theoryframework. Using a comparative methodology, this research examines the distinctive characteristics ofArabic noun phrases interact with the X-Bar theory. It also explores the consequences of these syntacticdifferences. This study sheds light on the syntactic examination of Arabic noun phrases within theframework of X-Bar theory. It also highlights the distinctions and similarities between Arabic andEnglish noun phrases. The fields of syntax, language typology, and linguistic variety will benefit greatlyfrom the study's conclusions.